Editorial - Editor (Hamdard Islamicus, 2021)
This is the fourth and last issue of the Hamdard Islamicus for 2020. With Allah’s Mercy, this research journal has successfully completed its 43rd year of publication without a single break. The current issue comprises five articles which cover a comparative study of the Holy Qur’?n’s text and William Shakespeare’s writings regarding four main vices of human being, analysis of the claim that Islam is a religion of peace, conception of Orthodoxy and Heresy in Islam, impact of Mu‘tazilah and romantic interpretation of religion.